The Influence of Motivation and Learning Style in the Effectiveness of Online Learning Through the Zoom Meeting Platform and Its Impact on Student Learning Outcomes at the Faculty of Economics and Business, Universitas Negeri Jakarta 2025 - Aulia, Putri; Taher, Sandy Hikmanudin; Usman, Osly (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
The purpose of this study is to find out how the learning style and motivation of students of the Faculty of Economics and Business of Universitas Negeri Jakarta affect how well they learn online through the Zoom Meeting platform and how it affects their learning outcomes. The major changes in the learning system caused by the COVID-19 pandemic led to the background of this study. This change encourages universities to use technology as the main learning tool. One of the most popular platforms, Zoom Meeting is still less effective in encouraging students and learning styles. In this study, a quantitative approach was used along with a survey. Data was collected through questionnaires distributed to one hundred active Universitas Negeri Jakarta Faculty of Economics and Business students. The analysis results show that learning motivation has a positive and significant effect on the effectiveness of online learning and student learning outcomes. This research found that high motivation to learn, methods that suit students' learning styles, and platforms such as Zoom Meeting are essential to achieve optimal online learning outcomes. The results of this study are expected to be a reference for students, teachers, and educational institutions to improve the quality of online learning in the future.